Associação entre mastigação e excesso de peso : uma revisão sistemática - Alves, Mariana Pexe (2014)
Overweight and obesity constitutes a worldwide public health issue, being an important risk factor for chronic non-transmitted diseases. Of multifactorial origin, it has the feeding behavior as an important etiological factor. Studies suggest that the control over food intake may be altered by mastication, since the masticatory process is a rich source of several impulses that stimulate the satiety center in the hypothalamus. Objectives: Systematic review of the literature about the association between mastication and overweight. Methodology: A systematic review was carried out in five databases (MEDLINE, Scopus, Web of Science, LILACS and ADOLEC), with no restriction regarding dates, language, journal or study design. The review followed the phases of study identification, selection and inclusion, according to previously defined eligibility criteria, independent of the direction of association, chewing is considered exposure or outcome. The EndNoteWeb software version 3 was used. Results: The database search detected 2496 publications, 23 of which were selected. In 14 of the 23 studies the BMI was treated as outcome and among them 11 suggest that there is a positive relationship between some mastication aspect analyzed (greater speed, smaller number of mastications per bite, less efficiency) and BMI. Of the nine articles that analyzed the BMI from the exposure point of view, five studies presented evidence of direct association between the BMI and mastication variables. Conclusion: The analysis shows that there is an association between chewing and overweight. Despite the heterogeneity found among the publications, it is clear that when there was a chewing alteration (lower strength, higher speed, lower efficiency), a higher BMI was found. However, one cannot determine the existence of a causal relationship between chewing and being overweight, since the available evidence is based on cross-sectional studies. The emphasis is therefore on the need for further studies to prospectively access this relationship.